Efforts to Improve Student Learning Outcomes in Islamic Education Learning by Using Audiovisual Media at SD Negeri Lamtheun Aceh Besar - M Yusuf; Putri Rahmi (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students’ learning outcomes in Islamic Education (Pendidikan Agama Islam/PAI) through the use of audiovisual media at SD Negeri Lamtheun, Aceh Besar. The research employed Classroom Action Research (CAR) consisting of two cycles, with each cycle including four stages: planning, action, observation, and reflection. The participants were 28 fifth-grade students. Data were collected through learning outcome tests, observation sheets of student learning activities, and teacher performance observation instruments. The results indicated a significant improvement in students’ academic achievement and classroom engagement after the implementation of audiovisual media. In the pre-cycle stage, the average student score was 62.14, with only 11 students (39.29%) achieving the Minimum Mastery Criteria (KKM = 75). After the implementation of audiovisual media in Cycle I, the average score increased to 73.21, with 18 students (64.29%) achieving mastery. Furthermore, in Cycle II, the average score rose to 84.46, and 25 students (89.29%) successfully met the KKM. Observational data also showed improvement in student learning activity, increasing from 61.50% in Cycle I to 86.25% in Cycle II, indicating higher participation, attention, and motivation during the learning process. These findings demonstrate that audiovisual media is effective in enhancing students’ understanding of Islamic Education materials, improving learning motivation, and strengthening learning outcomes. Therefore, audiovisual-based instruction can be recommended as an innovative and effective learning strategy to improve the quality of Islamic Education learning in elementary schools.